Intermediate-dose versus low-dose low-molecular-weight heparin in pregnant and post-partum women with a history of venous thromboembolism (Highlow study): an open-label, multicentre, randomised, controlled trial. Issue 10365 (19th November 2022) - Bistervels, Ingrid M; Buchmüller, Andrea; Wiegers, Hanke M G; Ní Áinle, Fionnuala; Tardy, Bernard; Donnelly, Jennifer; Verhamme, Peter; Jacobsen, Anne F; Hansen, Anette T; Rodger, Marc A; DeSancho, Maria T; Shmakov, Roman G; et al.
Summary: Background: Pregnancy-related venous thromboembolism is a leading cause of maternal morbidity and mortality, and thromboprophylaxis is indicated in pregnant and post-partum women with a history of venous thromboembolism. The optimal dose of low-molecular-weight heparin to prevent recurrent venous thromboembolism in pregnancy and the post-partum period is uncertain. Methods: In this open-label, randomised, controlled trial (Highlow), pregnant women with a history of venous thromboembolism were recruited from 70 hospitals in nine countries (the Netherlands, France, Ireland, Belgium, Norway, Denmark, Canada, the USA, and Russia). Women were eligible if they were aged 18 years or older with a history of objectively confirmed venous thromboembolism, and with a gestational age of 14 weeks or less. Eligible women were randomly assigned (1:1), before 14 weeks of gestational age, using a web-based system and permuted block randomisation (block size of six), stratified by centre, to either weight-adjusted intermediate-dose or fixed low-dose low-molecular-weight heparin subcutaneously once daily until 6 weeks post partum. The primary efficacy outcome was objectively confirmed venous thromboembolism (ie, deep-vein thrombosis, pulmonary embolism, or unusual site venous thrombosis), as determined by an independent central adjudication committee, in the intention-to-treat (ITT) population (ie, all women randomly assigned to treatment). The primary safety outcome was major bleeding which included antepartum, early post-partum (within 24 h after delivery), and late post-partum major bleeding (24 h or longer after delivery until 6 weeks post partum), assessed in all women who received at least one dose of assigned treatment and had a known end of treatment date. This study is registered with ClinicalTrials.gov, NCT01828697, and is now complete. Findings: Between April 24, 2013, and Oct 31, 2020, 1339 pregnant women were screened for eligibility, of whom 1110 were randomly assigned to weight-adjusted intermediate-dose (n=555) or fixed low-dose (n=555) low-molecular-weight heparin (ITT population). Venous thromboembolism occurred in 11 (2%) of 555 women in the weight-adjusted intermediate-dose group and in 16 (3%) of 555 in the fixed low-dose group (relative risk [RR] 0·69 [95% CI 0·32–1·47]; p=0·33). Venous thromboembolism occurred antepartum in five (1%) women in the intermediate-dose group and in five (1%) women in the low-dose group, and post partum in six (1%) women and 11 (2%) women. On-treatment major bleeding in the safety population (N=1045) occurred in 23 (4%) of 520 women in the intermediate-dose group and in 20 (4%) of 525 in the low-dose group (RR 1·16 [95% CI 0·65–2·09]). Interpretation: In women with a history of venous thromboembolism, weight-adjusted intermediate-dose low-molecular-weight heparin during the combined antepartum and post-partum periods was not associated with a lower risk of recurrence than fixed low-dose low-molecular-weight heparin. These results indicate that low-dose low-molecular-weight heparin for thromboprophylaxis during pregnancy is the appropriate dose for the prevention of pregnancy-related recurrent venous thromboembolism. Funding: French Ministry of Health, Health Research Board Ireland, GSK/Aspen, and Pfizer.